New facility for calibrating retroreflectometers - Miller, C. Cameron; Heimer, Todd.; Early, Edward; National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board; National Institute of Standards and Technology (U.S.). (Washington, DC Transportation Research Board, 2005)
"This digest announces the results of NCHRP Project 05-16, "National Calibration Facility for Retroreflective Traffic Control Materials." The research team (composed of C. Cameron Miller, Todd Heimer, and Edward Early, National Institute of Standards and Technology) established a center for the calibration of portable retroreflectometers used for measuring the retroreflectivity of pavement markings and signs"--P. [1].
Caption title.
"May 2005."
Also available online via the Transportation Research Board web site (http://trb.org/).
Keywords: Reflectometer -- Calibration; Reflectance -- Measurement -- Equipment and supplies; Road markings -- Testing -- Equipment and supplies